T Cell-Mediated Immune Responses to AAV and AAV Vectors - Ertl, Hildegund C. J. (Frontiers in Immunology, 2021)
Adeno-associated virus (AAV)-mediated gene transfer has benefited patients with inherited diseases, such as hemophilia B, by achieving long-term expression of the therapeutic transgene. Nevertheless, challenges remain due to rejection of AAV-transduced cells, which in some, but not all, patients can be prevented by immunosuppression. It is assumed that CD8+ T cells induced by natural infections with AAVs are recalled by the AAV vector’s capsid and upon activation eliminate cells expressing the degraded capsid antigens. Alternatively, it is feasible that AAV vectors, especially if given at high doses, induce de novo capsid- or transgene product-specific T cell responses. This chapter discusses CD8+ T cell responses to AAV infections and AAV gene transfer and avenues to prevent their activation or block their effector functions.